2022
DOI: 10.3389/fendo.2021.777130
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of COVID-19 Patients in a Regional Population With Diabetes Mellitus: The ACCREDIT Study

Abstract: ObjectiveTo identify clinical and biochemical characteristics associated with 7- & 30-day mortality and intensive care admission amongst diabetes patients admitted with COVID-19.Research Design and MethodsWe conducted a cohort study collecting data from medical notes of hospitalised people with diabetes and COVID-19 in 7 hospitals within the Mersey-Cheshire region from 1 January to 30 June 2020. We also explored the impact on inpatient diabetes team resources. Univariate and multivariate logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 23 publications
2
7
3
Order By: Relevance
“…Previous studies have found varying associations between HbA1c and COVID‐19‐related outcomes 3,18,21,23,24 . A large English study in primary care described a clear association between higher HbA1c in patients and COVID‐19‐related death, 3 but several other studies, including the present, have not been able to reproduce these findings 18,21,23,24 .…”
Section: Discussioncontrasting
confidence: 57%
“…Previous studies have found varying associations between HbA1c and COVID‐19‐related outcomes 3,18,21,23,24 . A large English study in primary care described a clear association between higher HbA1c in patients and COVID‐19‐related death, 3 but several other studies, including the present, have not been able to reproduce these findings 18,21,23,24 .…”
Section: Discussioncontrasting
confidence: 57%
“…The CORONADO study found that both microvascular (OR 2.14 [95% CI:1.16–3.94]) and macrovascular (OR 2.54 [95% CI: 1.44–4.50]) complications were independently associated with the risk of death on day seven of admission after adjusting for age, sex, comorbidities/complications, and glucose-lowering and anti-hypertensive treatment [ 13 , 14 , 19 ]. By contrast, no association was found between mortality (death by day seven of admission) and micro- or macrovascular complications in the ACCREDIT Study [ 15 ]. Nevertheless, both cohorts differ in several aspects such as mean age (69.8 in the CORONADO study vs. 74.1 for the ACCREDIT study cohort), median BMI (28.4 kg/m 2 vs. 27.6 kg/m 2 ), the mean HbA1c (8.1% vs. 7.7%), which may partially explain the different results regarding the outcomes [ 13 15 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, no association was found between mortality (death by day seven of admission) and micro- or macrovascular complications in the ACCREDIT Study [ 15 ]. Nevertheless, both cohorts differ in several aspects such as mean age (69.8 in the CORONADO study vs. 74.1 for the ACCREDIT study cohort), median BMI (28.4 kg/m 2 vs. 27.6 kg/m 2 ), the mean HbA1c (8.1% vs. 7.7%), which may partially explain the different results regarding the outcomes [ 13 15 , 19 ]. Our analysis suggests that participants living with diabetes hospitalized for COVID-19 with previous macrovascular complications (ischemic heart disease, stroke, peripheral artery disease) have an approximately 50% higher risk of mortality compared to people with no history of macrovascular disease after adjusting for all available confounding factors and that ischemic heart disease and stroke are the main contributors to this higher risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in ACCREDIT study, BMI, presence of DM complications, and glycemic control were not associated with mortality. However, higher CRP levels and advanced age were still predictive of 7-day mortality [62]. In a meta-analysis of laboratory predictors of poor outcome in diabetic COVID-19 patients, having higher levels of the inflammatory parameters, increased coagulation and cardiac activity markers, and lower lymphocyte count were associated with poor outcome [63].…”
Section: Diabetes Mellitus and Covid-19 Infectionmentioning
confidence: 99%